Association between CASC16 rs4784227 polymorphism and breast cancer susceptibility: A meta-analysis. Issue 28 (16th July 2021) - Liang, Xiong-Shun; Mo, Jun-Luan; Hu, Li-Ming; Gong, Chun-Mei; Liu, Tao; Hong, Wen-Xu; Yin, Ji-Ye; Liu, Zhao-Qian; Zhou, Hong-Hao
Abstract: Objective: To explore whether rs4784227 polymorphism of CASC16 is correlated with risk of breast cancer. Methods: Relevant studies up to December 24, 2020 were searched in PubMed, Embase, Web of Science, CNKI, VIP, and WANFANG databases. Data were analyzed by using Stata 12.0. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated, and country-based subgroup analyses were conducted. Sensitivity analysis was conducted to assess the stability of the results. Publication bias was assessed by using the Egger regression asymmetry test and visualization of funnel plots. Results: Seven case-control studies enrolling 4055 breast cancer cases and 4229 controls were included. rs4784227 was found significantly associated with increased risk of breast cancer in a dominant (OR = 1.301, 95% CI = 1.190–1.423, P < .001), a recessive (OR = 1.431, 95% CI = 1.216–1.685, P < .001), and an allele model (OR = 1.257, 95% CI = 1.172–1.348, P < .001), while an over-dominant model showed that rs4784227 was correlated with decreased breast cancer risk (OR = 0.852, 95% CI = 0.778–0.933, P = .001). Conclusion: The rs4784227 polymorphism of CASC16 gene is correlated with breast cancer susceptibility.